2020
DOI: 10.4209/aaqr.2020.07.0423
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Face Masks Made of Common Materials for General Public: Fractional Filtration Efficiency and Breathability Perspective

Abstract: As COVID-19 pandemic has caused more than 24 million confirmed cases globally (as of August 28 th , 2020), it is critical to slow down the spreading of SARS-CoV-2 to protect the healthcare system from overload. Wearing a respirator or a mask has been proven as an effective method to protect both the wearer and others, but commercially available respirators and masks should be reserved for healthcare workers under a currently desperate shortage. The use of alternative materials becomes an option for the general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 33 publications
(43 reference statements)
1
32
0
Order By: Relevance
“…When they travel further in the air, the droplets evaporate to significantly smaller size and the velocity relaxes close to the movement of the surrounding air. In view of the respiratory disease transmission, particles smaller than 10 µm (the size after droplets have reduced in size due to evaporation) pose more risk than larger ones since they are more likely to remain suspended in air 40 , to bypass a face shield, to penetrate through face masks / respirators [41][42][43] , and be inhaled and deposited in the respiratory tract. The residual particle size depends on the size and composition of the original droplets.…”
Section: Ultrasonic Scaler Aerosol Characterizationmentioning
confidence: 99%
“…When they travel further in the air, the droplets evaporate to significantly smaller size and the velocity relaxes close to the movement of the surrounding air. In view of the respiratory disease transmission, particles smaller than 10 µm (the size after droplets have reduced in size due to evaporation) pose more risk than larger ones since they are more likely to remain suspended in air 40 , to bypass a face shield, to penetrate through face masks / respirators [41][42][43] , and be inhaled and deposited in the respiratory tract. The residual particle size depends on the size and composition of the original droplets.…”
Section: Ultrasonic Scaler Aerosol Characterizationmentioning
confidence: 99%
“…Prior works on improvised materials found that common fabrics (sweatshirts, t-shirts, towels and scarfs) can block 10-60% percent of particles in the 0.2-1 µm range (Rengasamy et al 2010) and improves to 90% for the larger particle ranges (>1 µm) due to being in the inertial impaction regime (Konda et al 2020). Other studies have since examined various non-fabric filters, including HVAC filters, vacuum bags, paper towel, and sterilization wraps (300-wt) and found filtrations of between <60-87% at 0.3 um, 5-75% at 0.3 um, 36% at 2.75 um and 95% at 2.75 um, respectively (Pei et al 2020;Rogak et al 2020;Davies et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas some studies use a manikin headform with the full mask (Balazy et al, 2006a,b;He et al, 2013;Bahloul et al, 2014;Shakya et al, 2016;Adhikari et al, 2018;Kumar et al, 2020), other studies cut a portion of the mask/fabric and place it in a filter holder (Eshbaugh et al, 2008;Lin et al, 2017;Konda et al, 2020;Pei et al, 2020;Wang et al, 2020). Many studies use salt, e.g., NaCl (Eshbaugh et al, 2008;He et al, 2014;Lin et al, 2017;Pei et al, 2020), or polystyrene latex (PSL) spherical particles of defined sizes (Qian et al, 1997;Lee et al, 2005;Eshbaugh et al, 2008) to simulate particulate contaminants. The particle concentration used in these experiments varies from hundreds to several tens of thousands of particles per cm 3 (Balazy et al, 2006a,b;Eshbaugh et al, 2008;He et al, 2014;Adhikari et al, 2018).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…These two flow rates are equivalent to respiration at rest (~30 L min -1 ) and during exertion (~85 L min -1 ) (Lee et al, 2005;Bałazy et al, 2006a;He et al, 2014;Pei et al, 2020), considering the average surface area of an N95 (~200 cm 2 ) (Roberge et al, 2010) and the surface area of our test materials. In order to provide a fair comparison of the ability of each material to capture 250 nm PSL particles, all materials were tested at the same flow rate.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation